Analisis Pengaruh Kemampuan Intelektual terhadap Hasil Belajar Mahasiswa dengan Penggunaan Media E-Learning sebagai Variabel Intervening : (Studi Kasus Mahasiswa Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Putra Indonesia “YPTK” Padang) - Yuli Angraini (Universitas Veteran Bangun Nusantara, 2024)
Intellectual ability is the ability of an individual to carry out mental activities and think clearly based on knowledge. By utilizing technological developments present in the world of education, one of which is the use of E-learning media, students can better understand the material provided with several benefits such as efficiency and effectiveness. This research method was carried out on students from the Faculty of Economics and Business, majoring in Management, Putra Indonesia University